Pelaksanaan Usaha Kesehatan Sekolah di Sekolah Dasar Negeri 192 Pekanbaru - Hardianti, Sri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to describe the implementation of the School Health Efforts at SD N 192 Pekanbaru.There are 12 classes in the school with a total of 288 students. In this regard, the researcher wanted to find out how the implementation of the UKS which includes the TRIAS UKS and Little Doctor programs was in accordance with the guidebook for implementing UKS in schools. This research is a descriptive research with a qualitative research approach. The subjects in this study were the principal, two Physical Education teachers and 3 students as Little Doctors at SD N 192 Pekanbaru. Determination of the subjectin this study using a purposive technique. Data collection techniques used by observation, interviews and documentation. Checking the validity of the data in this study using triangulation. Data analysis techniques used qualitative analysis with data reduction, data display, and conclusion drawing (verification) steps. The results showed that the implementation of the UKS at SD N 192 Pekanbaru was successful and the majority went according to the UKS implementation guidebook published by the Ministry of Education and Culture, Directorate General of Basic Education in 2014. UKS activities were carried out curricularly and extracurricularly, with assistance from the Puskesmas school committee but there are still a number of activities in the guidebook that have not been implemented.